Submarine groundwater discharge and its impact on mangrove habitats in Dongzhaigang Area, Northeastern Hainan Island - Xianzhong KE; Xu ZHANG; Yanpeng ZHANG; Qinghua LI; Xianjun XIE; Wenfeng CHEN (Shuiwen dizhi gongcheng dizhi)
Submarine groundwater discharge (SGD) is a significant yet often overlooked pathway for material exchange between terrestrial and marine environments, delivering freshwater and nutrients to coastal ecosystems and influencing mangrove wetland health. Salinity balance and environmental quality are key factors in maintaining healthy mangrove habitats, yet the role of SGD in shaping these conditions in Dongzhaigang Area, northeastern Hainan, remains poorly understood. Moreover, the importance of groundwater considerations in mangrove ecological protection and restoration requires further exploration. This study investigated SGD characteristics and its ecological impacts on mangrove wetlands in Dongzhaigang Area using radon isotope (²²²Rn) as a natural tracer. The spatial and temporal variations of seawater 222Rn activity and its influencing factors were analyzed. Based on the 222Rn mass-balance model, the fluxes of SGD and the associated nutrients in Dongzhaigang Area were estimated. The findings indicate that the variation in 222Rn activity is predominantly influenced by the seasonal rainfall, tidal water level fluctuation, fracture zone structure, and the nature of surface sediments. Using the 222Rn mass balance model for the region, SGD fluxes were estimated to be 8.90×105 m3/d and 6.84×105 m3/d in the wet season and dry season, respectively; SGD-driven nutrient fluxes were estimated by combining the solute concentrations in groundwater. The fluxes of phosphate, nitrite, and nitrate were estimated to be 6440 kg/d, 53.44 kg/d, and 1084 kg/d, respectively, in the wet season—approximately two-thirds of these values in the dry season. The estimated SGD fluxes of the mangrove wetland in Dongzhaigang Area are comparable to the local river discharge, and the associated nutrient fluxes carried by the wetland were very significant; the hot and cold zones of SGD fluxes corresponded to the sparse and lush zones of the mangrove forests, respectively, suggesting that SGD may negatively affect mangrove wetland habitats in Dongzhaigang Area by reducing mangrove wetland salinity or environmental quality. This study provides a theoretical basis for the ecological protection and restoration of mangrove wetlands in Dongzhaigang Area.